Az árvizek hosszú távú hatásainak vizsgálata magyarországi árvíz-veszélyeztetett közösségekben = Long term effects of floods in flood-prone Hungarian communities - Molnár, András (Közép-Európai Közlemények, 2018)
Record level floods have long lasting effects on local communities and individuals, who experienced them. Depending on the actual circumstances these events might put people to “live in the fear of rain”, but the massive response and recovery efforts, that communities could observe and benefit from external sources could generate a false sense of safety. As the number of floods is expected to increase in the future, it is important to understand, how local communities cope with the burden of such events on a longer run. Floods are the most common disasters worldwide, both in terms of population and number of affected countries. Hydro meteorological disasters have strong European relevance due their impacts on member states, communities and regional policy issues. For Europe, floods are considered to be one of the most important natural hazards challenging local communities and member state response capacities. However the topic has strong contemporary policy relevance, there is small understanding on the unequal distribution of flood effects, and the long term changes and ramifications are still to be researched. Having a better understanding on the long term effects is an important base for long term planning of adaptation and resilience development measures. As part of a practical project focusing on the development of resilience among urban communities, this current research included focus groups in flood experienced urban communities. Following the framework provided by the Psychosocial Support Centre of Red Cross Red Crescent, this paper demonstrates the different results from two urban areas in Hungary. Using data collected during the focus group discussions I was able to draw two contradictory pathways how a community and its members could react on the long run to a historical flooding event.